Colour Stabilization of Oak, Spruce, Larch and Douglas Fir Heartwood Treated with Mixtures of Nanoparticle Dispersions and UV-Stabilizers after Exposure to UV and VIS-Radiation - Pánek, Miloš; Oberhofnerová, Eliška; Hýsek, Štěpán; Šedivka, Přemysl; Zeidler, Aleš (Materials (Basel, Switzerland), 2018)
Colour changes and associated wood degradation in exterior and interior applications influenced by ultraviolet (UV) and visible radiation (VIS) decreases the aesthetic value of the products and shortens the overall life of transparent coatings. The aim of the paper is to achieve colour stabilization of oak, larch, Douglas fir and spruce heartwood via surface treatment with UV stabilizers, hindered amine light stabilizers (HALS), nanoparticles TiO₂, ZnO, and mixtures thereof, during exposure to UV and VIS radiation. Colour changes were evaluated during accelerated artificial ageing testing in Xenotest. The distinctly individual character of colour changes in surface treatments due to the underlying wood species was confirmed. A synergistic effect was found when using a combination of active substances compared to substances used individually. The mixture of benzotriazoles with HALS (Tinuvin 5151) in combination with TiO₂ and ZnO nanoparticles was confirmed as one of the most effective treatments for colour stabilization of wood due to UV and VIS spectrums.
Keywords: colour stabilization; wood; surface treatment; accelerated ageing